UNDERSTANDING ORGANISATIONAL CULTURES - Karen Cacciattolo (European Scientific Journal, ESJ, 2014)
The paper aims to offer a better understanding of the various types of organisational culture. A brief introduction discusses the two main approaches for analyzing the culture of an organisation and includes the web model of Johnson & Scholes and the definitions of Charles Handy. The paper also presents the various classifications, levels and structures of organisational culture, namely those of Hofstede, Schein, Trompenaars, and Deal & Kennedy. All of these classifications, levels and structures offer an explanation of how an organisational culture works and the various definitions are included to enhance the meaning and how cultures work.